Information needs and knowledge sharing as correlate to knowledge utilization among Medical Practitioners in selected Teaching Hospitals in the South-West, Nigeria - Adewuyi, Olugbenga W.; Adekanye, Elizabeth A.; Nduka, Stella C. (Qualitative and Quantitative Methods in Libraries, 2019)
The paper examined the relationship between information needs, knowledge sharing and knowledge utilization among medical practitioners in selected Teaching Hospitals in South West, Nigeria. Descriptive survey research design was used for the study and pre-tested and validated questionnaire was employed as research instrument. The paper was discussed under the following sub-headings; Knowledge management life cycle in organizations and information needs. By extension, the paper strongly argued that there is a great nexus between information needs and other sub-sets of knowledge management vis-a-vis knowledge creation, knowledge sharing, storage of knowledge and knowledge utilization. The paper was guided by three objectives, three research questions and two hypothesises. It was discovered that information needs, knowledge sharing and knowledge utilization of the respondents were very high and that there was significant relationship among all the tested variables. The paper recommended that management in Nigerian Teaching Hospitals should create knowledge bank that will enhance information accessibility, knowledge sharing and knowledge utilization among staff as this will go a long way of improving health care service delivery.